Five questions on the multisensory perception in historic urban areas - Septianto, Eggi; Firmansyah, Firmansyah; Poerbo, Heru Wibowo; Martokusumo, Widjaja (SINERGI, 2025)
Multisensory perception is essential for individuals or communities to fully appreciate urban historic areas. Recognizing non-physical aspects such as sound, smell, and tactile sensations based on human senses is crucial for enhancing the relationship between individuals and their environment. Discussions on heritage conservation extend beyond physical aspects evaluated visually to encompass non-physical elements. This article presents five questions covering the definition, influencing factors, types and categories, and methods for multisensory perception research. Furthermore, this article aims to explain gaps in multisensory research in urban historic areas to determine what and how future heritage conservation studies should be conducted. The research employs content analysis methods to analyze discussions from selected literature regarding the benefits of multisensory research in urban historic areas. Multisensory perception significantly influences the diverse sensory experience of intangible aspects in an environment, enriching urban heritage conservation approaches.